2014
DOI: 10.1155/2014/837891
|View full text |Cite
|
Sign up to set email alerts
|

Colorful World of Microbes: Carotenoids and Their Applications

Abstract: Microbial cells accumulate pigments under certain culture conditions, which have very important industrial applications. Microorganisms can serve as sources of carotenoids, the most widespread group of naturally occurring pigments. More than 750 structurally different yellow, orange, and red colored molecules are found in both eukaryotes and prokaryotes with an estimated market of $ 919 million by 2015. Carotenoids protect cells against photooxidative damage and hence found important applications in environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 79 publications
0
110
0
10
Order By: Relevance
“…Moreover, such pigments are also found to possess antagonistic properties and natural pigments have a wide demand as antimicrobial agent in food preservation compared to synthetic pigments because of their low toxicity and decomposing nature (Nakamura et al, 2003). Carotenoids like zeaxanthin from rose hips, lutein from golden delicious apple, astaxanthin from Haematococcus pluvialis were found to be potent antimicrobial agents (Kirti et al, 2014;Horváth et al, 2012).…”
Section: Tablementioning
confidence: 99%
“…Moreover, such pigments are also found to possess antagonistic properties and natural pigments have a wide demand as antimicrobial agent in food preservation compared to synthetic pigments because of their low toxicity and decomposing nature (Nakamura et al, 2003). Carotenoids like zeaxanthin from rose hips, lutein from golden delicious apple, astaxanthin from Haematococcus pluvialis were found to be potent antimicrobial agents (Kirti et al, 2014;Horváth et al, 2012).…”
Section: Tablementioning
confidence: 99%
“…Puspha et al (2009) reported the antimicrobial activity of total red pigment fr o m Mo n a scu s pu rpu reu s MT CC 4 10 recorded more antimicrobial activity, which could yield significant information on the scope for Monascus pigments substituted or as an adjunct to chemotherapeutic agents. Astaxanthin has also health benefits in cardiovascular disease prevention, immune system boosting, bioactivity against Helicobacter pylori, and cataract prevention due to its high antioxidant activity (Kirti et al, 2014). The development of novel drugs against drug resistant pathogen is the need of the hour.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly produced from fats by plants, bacteria and some fungi. Carotenoids have many applications including as colorants, food supplements and cosmetics/nutraceuticals [114]. Notably, carotenoids have antioxidant and anti-inflammatory properties that contribute to skin photo-protection through inhibition of UVA-induced ROS toxicity and enter in the formulation of many sunscreens [115].…”
Section: Antioxidantmentioning
confidence: 99%